Determinan Ekspor Industri Kecil dan Menengah Penerima Fasilitas Kemudahan Impor Tujuan Ekspor (KITE) - Guntara, Ronald; Muchtar, Masruri (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
The fluctuations in export value over the past few years caused Indonesia’s trade balance to be in deficit in 2018 and 2019. Through duty drawback policy to small and medium industry (KITE IKM), the government provides facilities to boost exports. This study aims to determine the effect of KITE IKM, rupiah exchange rate, Gross Domestic Product (GDP), inflation, and COVID-19 on the export value of KITE IKM. The method used is quantitative method, with secondary data from Directorate General of Customs and Excise (DJBC) and Central Bureau of Statistics (BPS) from March 2017 to December 2020. The data is processed with multiple linear regression analysis using a time series dataset of 46 months. The results showed that KITE IKM, rupiah exchange rate, and GDP had a significant positive effect, while inflation had no significant effect and COVID-19 had a significant negative effect on the export value of KITE IKM. The study concludes that the KITE IKM facility should be maintained and further developed because it enhances exports. The government is expected to stabilize the rupiah exchange rate, GDP, and inflation at levels that promote exports. Relaxation is needed, such as extending the export period in using KITE IKM facilities during the pandemic.